2020
DOI: 10.1016/j.heliyon.2020.e04758
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the environmental impact assessment practice in Uganda: challenges and opportunities for achieving sustainable development

Abstract: Environmental Impact Assessment (EIA) is a broad process that emerged from the National Environment Policy Act, 1970 in the U.S. Its primary objective is to generate information on the likely impacts of a project on all aspects of the environment and used in agency decision making and in the long run protect the environment and achieve sustainable development. EIA practice in Uganda was formally established through the National Environment Act, 1995 and now in practice for over 25 years. However, there is incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…To establish criteria by which to assess the ESIA system in Uganda, reviews of EIA in different countries around the world were considered (including Wood 2003 ;Ecaat 2004;Nadeem and Hameed 2008;Ahmadvand et al 2009;Dominik et al 2010;Kahangirwe 2011;Momtaz and Kabir 2013;Kamijo and Huang 2016;Aung 2017;George et al 2020). This revealed that a wide range of criteria has been used, varying according to the objectives of each research team.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To establish criteria by which to assess the ESIA system in Uganda, reviews of EIA in different countries around the world were considered (including Wood 2003 ;Ecaat 2004;Nadeem and Hameed 2008;Ahmadvand et al 2009;Dominik et al 2010;Kahangirwe 2011;Momtaz and Kabir 2013;Kamijo and Huang 2016;Aung 2017;George et al 2020). This revealed that a wide range of criteria has been used, varying according to the objectives of each research team.…”
Section: Methodsmentioning
confidence: 99%
“…Despite all this detail in the National Environment Act, the EIA Regulations and the Guidelines, there are many shortcomings in the ESIA process in Uganda (Ecaat 2004;Kahangirwe 2011;George et al 2020), hence the need to assess the Ugandan ESIA system and make recommendations to improve ESIA practice.…”
Section: Esia In Ugandamentioning
confidence: 99%
See 2 more Smart Citations
“…The focus on environmental sustainability has manifested in various ways, such as reducing energy consumption, recycling and/or reducing waste, reusing materials, adopting more sustainable building design and personal lifestyles [ 3 , 4 , 5 , 6 , 7 ]. An important dimension of the global drive to be environmentally sustainable is developing technological solutions, particularly solutions that enable greener power generation (e.g., waste-to-power generation, solar technology, wind turbines) [ 8 , 9 , 10 , 11 , 12 , 13 ]. This research focuses on the potential of a new technology – Solar Paver – to be successfully implemented to enable the sustainable generation of power.…”
Section: Introductionmentioning
confidence: 99%